Traditional Games as Cultural Heritage: The Case of Canary Islands (Spain) From an Ethnomotor Perspective - Luchoro-Parrilla, Rafael; Lavega-Burgués, Pere; Damian-Silva, Sabrine; Prat, Queralt; Sáez de Ocáriz, Unai; Ormo-Ribes, Enric; Pic, Miguel (Frontiers in Psychology, 2021)
UNESCO in the 2030 agenda for sustainable development establishes respect for the environment and sustainability education as key elements for the challenges of society in the coming years. In the educational context, physical education can have a vital role in sustainability education, through Traditional Sporting Games (TSG). The aim of this research was to study from an ethnomotor perspective the different characteristics of two different groups of TSG (with and without objects) in the Canary Islands, Spain. The corpus of this investigation was made up of 513 TSG, identified by two analysis techniques and collected in a database. The categories corresponding to the variables of the internal logic of the game were the type of motor interaction, related to space, relationships with time (competition), and relationships with objects. The study also examined the variables of external logic or sociocultural conditions such as the protagonists, playing areas, and game moments. The data analysis was carried out using descriptive and inferential statistics: cross-tables, effect sizes, classification trees (CHAID), and the identification of frequency areas. Of the total number of playful activities identified (n = 664), most were physical activities (n = 513/664; 77.26%) (non-physical activities: n = 151/664; 22.74%). These activities were Quasi-games without rules (n = 87) and TSG (n = 426) as well as activities with Objects (n = 299) and without material (n = 214). This research confirms that the TSG in the Canary Islands is a mirror of traditional culture and, from a pedagogical approach, shows great potential for material and social sustainability.